An Efficient Operant Choice Procedure for Assessing Delay Discounting in Humans: Initial Validation in Cocaine-Dependent and Control Individuals - Johnson, Matthew W. (2012)
Delay discounting is the decline in a consequence's control of behavior as a function of its delay, and may be a fundamental behavioral process in drug dependence. Human delay-discounting studies have usually relied on choices between hypothetical rewards. Some human tasks have assessed delay discounting using operant procedures with consequences provided during the task, as in nonhuman animal studies. However, these tasks have limitations such as long duration, potentially indeterminate data, or confounding the effect of delay with probability. A study in 20 cocaine-dependent volunteers and 20 demographically matched non-cocaine-dependent volunteers was designed to investigate a novel operant delay-discounting task providing monetary reinforcement by coin delivery throughout the task (Quick Discounting Operant Task; QDOT). Participants completed a hypothetical delay-discounting procedure, a potentially real reward delay-discounting procedure, and an existing operant delay-discounting task: the Experiential Discounting Task (EDT). The QDOT resulted in complete data for all participants, showed systematic effects of delay that were well described by a hyperbolic function, had a maximum duration of 17 min, and resulted in relatively little variability in session earnings. QDOT performance was significantly, positively correlated with performance on the EDT but not the other tasks. The QDOT resulted in an effect size between the groups that was similar to most other delay discounting tasks examined, and showed the cocaine-dependent participants to delay discount significantly more than the control participants. The QDOT is an efficient operant human delay-discounting task that may be useful in a variety of experimental settings.